Multiaxial fatigue of cast aluminium EN AC-42000 T6 (G-AlSi7Mg0.3 T6) for automotive safety components under constant and variable amplitude loading - C.M. Sonsino; R. Franz (Fracture and Structural Integrity)
Regarding the fatigue behaviour of EN AC-42000 T6 (A 356 T6), which is the most frequently used cast aluminium alloy for automotive safety components, especially under non-proportional constant and variable normal and shear stress amplitudes with changing principal stress directions, a poor level of knowledge was available. The reported investigations show that, under non-proportional normal and shear stresses, fatigue life is increased in contrast to ductile steels where life is reduced due to changing principal stress directions. This behaviour caused by the low ductility of this alloy (e < 10%) compared to quenched and tempered steels suggests the application of the Normal (Principal) Stress Hypothesis (NSH). For all of the investigated stress states under multiaxial constant and variable (Gaussian spectrum) amplitudes without and with mean stresses, the NSH was able to depict the life increase by the non-proportionality and delivered, for most cases, conservative but non-exaggerated results.